Implementasi Praktik (Rahn) Gadai Motor dalam Perspektif Hukum Ekonomi Syariah: Studi Kasus di Gg Waru IV Sukabumi Indah, Kota Bandar Lampung - Uswatun Hasanah; Miswanto; Susi Nurkholidah; Wulan Fitri Utami; Devina Putri Azara (Economic Reviews Journal, 2025)
Pawn is a process whereby an item deemed valuable according to religious law is used as collateral for a debt. In this way, individuals can borrow money or utilize a portion of the item. In Indonesia, the practice of pawning is very common because it is easy and simple to implement. However, people still do not understand the correct rules regarding pawning in Islam. The research conducted by the author falls into the category of field research. The approach chosen is juridical sociological. Interviews were used to collect primary data, while secondary data were obtained from library sources, such as books, journals, theses, and other references related to this research. The data collection methods applied include observation, interviews, and documentation. The focus of this research is to: 1) Identify how the vehicle pawn transaction process in Gg Waru IV Sukabumi Indah, Bandar Lampung City? 2) And to find out whether this pawn transaction is in accordance with the principles of Sharia economic law?